Technology of Processing Plant Extracts Using an Aluminometasilicate Porous Carrier into a Solid Dosage Form - Kostelanská, Klára; Kurhajec, Slavomír; Pavloková, Sylvie; Vetchý, David; Gajdziok, Jan; Franc, Aleš (Pharmaceutics, 2022)
A method of preparing tablets called liquisolid technique is currently emerging. In these formulations, an important role is played by porous carriers, which are the basic building blocks of liquisolid systems (LSSs). The most common are microcrystalline cellulose (MCC), magnesium aluminometasilicates, silica aerogels, mesoporous silicates, clays, etc. In this study, magnesium aluminometasilicate is used to prepare modified LSS formulations with plant extracts as model drugs dissolved in water (W) or ethanol (E). The modification involves drying tablets in a microwave (MW) and hot air dryer (HA) for a specified period. Powder blends and tablets were evaluated for physical properties, and their antioxidant activity (AA) was measured in a modified dissolution by ferric reducing antioxidant power assay (FRAP). PLS and ANOVA were used to compare tablets properties depending on the composition and technology. The experiment is based on a previous one, in which the plant extracts were processed into tablets using a similar method. Therefore, extending the study to include more plants and the robust statistical evaluation and comparison of the products was a procedure to justify the suitability of the presented method for a wide range of liquid plant extracts. As a result, we obtained tablets with excellent physical properties, including a short disintegration and dissolution, which is problematic in tableted extracts.